Is Investment Intention Affected by Financial Literacy, Financial Knowledge, Motivation, and Technological Developments? - Subagiyo, Rokhmat; Budiman, Ahmad; Domastuti, Putri; Bachtiar, Jusuf; Ridlwan, Ahmad Ajib (Univeristas Islam Bandung, 2023)
Investor intends to put some of one's money in the stock market with the hope of future profits. This study aims to examine the development of technology as an intervention variable for financial literacy, financial knowledge, and motivation on investment intention. This research method provides a quantitative with an associative approach. Data was collected using survey, then analysed using PLS-SEM with WarpPLS. The results show that financial literacy, financial knowledge, and motivation affect students investment intention. However, motivation does not affect investment intention influence technological developments.